2016
DOI: 10.1002/adma.201506065
|View full text |Cite
|
Sign up to set email alerts
|

Sky‐Blue Phosphorescent OLEDs with 34.1% External Quantum Efficiency Using a Low Refractive Index Electron Transporting Layer

Abstract: Blue-phosphorescent organic light-emitting diodes (OLEDs) with 34.1% external quantum efficiency (EQE) and 79.6 lm W(-1) are demonstrated using a hole-transporting layer and electron-transporting layer with low refractive index values. Using optical simulations, it is predicted that outcoupling efficiencies with EQEs > 60% can be achieved if organic layers with a refractive index of 1.5 are used for OLEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(166 citation statements)
references
References 38 publications
6
153
0
1
Order By: Relevance
“…Among all the emitting materials developed for OLEDs, phosphorescent transition metal complexes, e.g., Ir(III) and Pt(II) complexes, have drawn great attention due to their capability of harvesting 100% of the both singlet and triplet excitons electrogenerated in devices 6, 7. Using Ir(III) complexes as emitters, blue, green, and orange OLEDs with external quantum efficiencies (EQEs) over 30% have been reported 8, 9, 10, 11, 12. However, even based on elaborately designed bipolar host materials and sophisticated device structures, only several most efficient vacuum‐deposited red OLEDs using Ir(III) complexes as emitters show EQEs around 26% 11, 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the emitting materials developed for OLEDs, phosphorescent transition metal complexes, e.g., Ir(III) and Pt(II) complexes, have drawn great attention due to their capability of harvesting 100% of the both singlet and triplet excitons electrogenerated in devices 6, 7. Using Ir(III) complexes as emitters, blue, green, and orange OLEDs with external quantum efficiencies (EQEs) over 30% have been reported 8, 9, 10, 11, 12. However, even based on elaborately designed bipolar host materials and sophisticated device structures, only several most efficient vacuum‐deposited red OLEDs using Ir(III) complexes as emitters show EQEs around 26% 11, 13, 14, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Utilization of TADF emitters provide an opportunity not only to reduce the overreliance on expensive precious metals for efficient OLEDs, but also to solve the urgent issue of developing stable and efficient blue materials and their devices. [2][3][4][10][11][12][13] While great progress has been made,s ome key challenges remain to be tackled. [2][3][4][10][11][12][13] While great progress has been made,s ome key challenges remain to be tackled.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that higher out-coupling effi ciencies can be achieved [ 23,24 ] and in some cases the formation of a cross-section of singlet to triplet excitons may be different from that generally calculated in classical statistics. Therefore, it may have possibly resulted from an improved out-coupling effi ciency or singlet-generation fraction.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 93%